Front Cover: A Promiscuous Cytochrome P450 Hydroxylates Aliphatic and Aromatic C−H Bonds of Aromatic 2, 5‐Diketopiperazines (ChemBioChem 8/2019). (26th March 2019) - Jiang, Guangde; Zhang, Yi; Powell, Magan M.; Hylton, Sarah M.; Hiller, Nicholas W.; Loria, Rosemary; Ding, Yousong
Abstract : The front cover picture shows a versatile biocatalytic synthesis of hydroxylated di‐N‐methylated aromatic diketopiperazines (ADKPs). Di‐N‐methylated ADKPs were synthesized from two amino acids with TxtA and TxtB (yellow) from Streptomyces scabies, or from ADKP with one N ‐methyltransferase Amir_4628 (green) from Actinosynnema mirum . Human methionine adenosyltransferase hMAT2A (purple) was recruited to synthesize the methyl donor SAM. The P450 TxtC (pink) along with the NADPH‐recycling glucose dehydrogenase (cyan) from Bacillus subtilis promoted aliphatic and/or aromatic C−H hydroxylation on di‐N‐methylated ADKPs. More information can be found in the full paper by Y. Ding et al. on page 1068 in Issue 8, 2019 (DOI: 10.1002/cbic.201800736 ).